College Women's Experiences With Rape Disclosure: A National Study. (April 2013) - Paul, Lisa A.; Walsh, Kate; McCauley, Jenna L.; Ruggiero, Kenneth J.; Resnick, Heidi S.; Kilpatrick, Dean G.
Disclosure of a rape to informal support sources (e.g., friends) is a relatively common experience, but it is not well understood. This study expands our limited knowledge of the characteristics and life experiences of disclosure recipients among a national sample of 2, 000 female college students. Over 40% of respondents reported having received a rape disclosure, and more than two thirds of these recipients encouraged victims to formally report their rapes to the police or other authorities. Correlates of disclosure receipt and encouragement of reporting, including personal assault history, mental health history, and substance use, are presented and discussed.